The influence of training and work motivation on employee performance at PT. Iss Indonesia Pondok Indah Mall South Jakarta - Sampoerno, M. Rizki; Pari, H. Fauzie; Rasyid, Muhammad; Satriani, Desi (Junal Ilmu Manajemen, 2024)
The aim of this research is to determine the partial or simultaneous influence of Training and Work Motivation on Employee Performance at PT ISS Indonesia Pondok Indah Mall, South Jakarta. This research method is quantitative with a sample of 60 people. The data analysis method uses validity tests, reliability tests, classical assumption tests, multiple linear regression analysis tests, correlation tests, determination tests, t tests and f tests. The results of this research are that training has a significant effect on employee performance, work motivation has a significant effect on employee performance. Meanwhile, training and work motivation simultaneously influence employee performance.